Children’s Momentary Behavioural Engagement and Class Size: A National Systematic Observation Study : Momentary Behavioural Engagement - Symonds, Jennifer; Boheim, Ricardo; Somerville, Matthew; Baines, Edward; Tang, Xin; Oeri, Niamh; Rinas, Raven; Buehler, Florian; Benke, Gertraud; Davies, Aisling; Sloan, Seaneen; Devine, Dympna; et al. (Frontline Learning Research, 2025)
This study used systematic observation to test the direct and moderating effects of class size on children’s momentary behavioural engagement in learning. Data were collected with 632 children (50.6% girls) in 121 classrooms in 92 schools recruited into the Children’s School Lives national cohort study of Irish primary schooling. The Observational and Research Classroom Learning Evaluation (ORACLE) systematic observation tool was used to observe individual children’s behaviour at 30-seconds intervals across a five-minute period in ordinary lessons of English, mathematics, science and Irish. Multilevel path models identified that behavioural engagement was higher in smaller classes and behavioural disengagement was higher in larger classes. Class size also moderated the impact of several individual differences and classroom composition factors on momentary behavioural engagement. For example, smaller classrooms protected lower ability children from disengaging whereas higher ability children were more likely to stay engaged in larger classes compared to lower ability children. Implications for research, practice and policy are discussed.